2014
DOI: 10.3390/molecules191221034
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Anthocyanins from Red Grape Skins under Pressurized Liquid Extraction and Ultrasound-Assisted Extraction Conditions

Abstract: Abstract:The stability of anthocyanins from grape skins after applying different extraction techniques has been determined. The following compounds, previously extracted from real samples, were assessed: delphinidin 3-glucoside, cyanidin 3-glucoside, petunidin 3-glucoside, peonidin 3-glucoside, malvidin 3-glucoside, peonidin 3-acetylglucoside, malvidin 3-acetylglucoside, malvidin 3-caffeoylglucoside, petunidin 3-p-coumaroylglucoside and malvidin 3-p-coumaroylglucoside (trans). The techniques used were ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 15 publications
4
18
0
1
Order By: Relevance
“…By opposition, the main limitations often reported are the low selectivity towards the analytes during extraction, and many interferents may be extracted during the extraction process, an exaggerated dilution of the analytes, especially when a large number of cycles are used, and the high requirements in instrumentation, which increases their costs [103][104][105]. However, these limitations in PLE are a well-known extraction technique and have been used for the extraction of polyphenols from several diferent matrices [106][107][108][109][110][111].…”
Section: Pressurized Liquid Extraction (Ple)mentioning
confidence: 99%
“…By opposition, the main limitations often reported are the low selectivity towards the analytes during extraction, and many interferents may be extracted during the extraction process, an exaggerated dilution of the analytes, especially when a large number of cycles are used, and the high requirements in instrumentation, which increases their costs [103][104][105]. However, these limitations in PLE are a well-known extraction technique and have been used for the extraction of polyphenols from several diferent matrices [106][107][108][109][110][111].…”
Section: Pressurized Liquid Extraction (Ple)mentioning
confidence: 99%
“…Comparison of the stability of anthocyanins extracted from the grape skin by the subcritical extraction together with ultrasound with the results obtained by microwave extraction showed that the effect of temperature and the resistance of anthocyanins are different [17].…”
Section: Literature Review and Problem Statementmentioning
confidence: 95%
“…Additionally, anthocyanins are considered to be nontoxic and safe additives (Pina et al, 2012). However, there are some limitations for commercial uses of anthocyanins due to the availability of feedstocks (quantity and quality), difficulty in purifying the extracts, the high cost of raw materials and low stability during processing and storage (Del Pozo-Insfran et al, 2004;Liazid et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanins are relatively unstable pigments, and temperature is the main factor that triggers the degradation of the anthocyanins. Dther factors, such as their chemical structure, pH, presence of light, ions, enzymes or oxygen, can trigger their degradation (Liazid et al, 2014;Sui et al, 2014). However, the color stability of the anthocyanins is increased under acid presence due to the antibrowning effects (Altunkaya & Gökmen, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation